Synthesis of Cellulose Nanocrystals from Rice Husk Using Nitric Acid Hydrolysis - Fernanda, Moza Ayu; Novianah, Delia Indah; Siswati, Nana Dyah; Pujiastuti, Caecilia (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Rice husk residue has excellent potential as a raw material for making cellulose nanocrystals because of its relatively high cellulose content. This research focuses on determining the most effective hydrolysis conditions, especially the reaction time and nitric acid (HNO₃) content, in the synthesis of cellulose nanocrystals. This study also aims to determine the effect of variations in nitric acid concentration and hydrolysis time on the amount of product produced (yield) and the final size of cellulose nanocrystals. The process of making these nanocrystals involves three main stages, namely the removal of lignin using a 17,5% NaOH solution, followed by annealing using a 10% H₂O₂ solution, and finally breaking the cellulose bonds (acid hydrolysis) with a concentrated nitric acid solution of between 2% and 6% for different time periods (30 to 15 minutes). Product characterization using FT-IR and SEM has been carried out to confirm the presence of cellulose and determine the size of the nanocrystals formed. Experimental results show that the smallest cellulose crystal size achieved is between 0,93 to 65,10 μm, which was obtained through hydrolysis using 6% nitric acid for 150 minutes.